7 - Lieux de vente de vin de palme et débats publics : une autre face de l’espace public à Kisangani - Lipambala, John Nkoko (Africa Development, 2021)
In Kisangani, unfavourable socioeconomic conditions lead some people to let off steam in premises where palm wine, known as libondo in the local jargon, is consumed. Such premises have become places where men and women meet after market, after work or after they have finished working in the fields. In addition to drinking palm wine, whose cost fits every budget, the people who frequent these places take advantage of the atmosphere that prevails there to express their views on the major issues of the city, the province, the country or even the planet. In their view, the right information is passed on in such places. Thus, in Kisangani, points of sale of libondo have become public spaces where debates and discussions are organized, spontaneously and informally, on topical issues. Anything can be said in these places and there are no taboo subjects or security constraints. This is because the people there believe they are with others who share the same standard of living and thus the same hardships. Accordingly, they should not cause problems for one another; on the contrary, these places must be seen as the only chance for freedom of expression.